Survei Standarisasi Sarana dan Prasarana Olahraga Bulutangkis, Renang, Tenis Meja di DISPAPOR Kabupaten Cilacap - PRATOMO, TRI BAGUS; Yuwono, Cahyo (Universitas Negeri Semarang, 2023)
The purpose of this study was to find out how the standardization of facilities and infrastructure for badminton, swimming, table tennis in Cilacap Regency. This research uses a qualitative approach. The subject of this research is the head of the field of sports infrastructure, field manager, coach. The research data collection technique used the method of observation, interviews, and documentation. Technical analysis of the data carried out includes data collection, data reduction, and drawing conclusions. The validity of the data in this study used data triangulation. The results of the research on badminton facilities and infrastructure are suitable for training and organizing championships up to the national level. Swimming facilities and infrastructure are only suitable for use for training, while for organizing championships they are not suitable for use. Because swimming facilities and infrastructure are not yet owned by the Regency government, but are owned by the private sector. Table tennis facilities and infrastructure are only suitable for training and holding championships up to the National level. The conclusions of this research are, Standardization of facilities and infrastructure for badminton, swimming, table tennis at DISPORAPAR Cilacap Regency in 2021 is included in the criteria quite feasible.